Higher adenoma detection rates with cap-assisted colonoscopy: a randomised controlled trial - Rastogi, Amit; Bansal, Ajay; Rao, Deepthi S; Gupta, Neil; Wani, Sachin B; Shipe, Tracy; Gaddam, Srinivas; Singh, Vikas; Sharma, Prateek (Gut, 2012)
ObjectiveCap-assisted colonoscopy (CAC) uses a small plastic transparent cap attached to the tip of the colonoscope that can depress and flatten colonic folds and thus improve visualisation of their proximal aspects. The aim of this study was to compare CAC with standard colonoscopy (SC; high-definition white light) for adenoma detection rates.DesignThis is a prospective randomised controlled trial.SettingThe study was performed in a tertiary-care Veterans Affairs Medical Center in the USA.PatientsSubjects undergoing screening or surveillance colonoscopy were enrolled.InterventionsSubjects were randomised to undergo either CAC or SC.Main outcome measuresThe outcome measures were the proportion of subjects with at least one adenoma, the number of adenomas detected per subject, insertion time, caecal intubation rates and complications.Results420 subjects were enrolled and included in the study (210 in each group). The proportion of subjects with at least one adenoma was higher with CAC compared to SC (69% vs 56%, p=0.009). CAC also detected a higher number of adenomas per subject (2.3 vs 1.4, p<0.001). The caecal intubation time was shorter with CAC (3.29 min vs 3.98 min, p<0.001). The caecal intubation rates were similar in the two groups (99% vs 98%, p=0.37). There were no complications associated with CAC or SC.ConclusionsCAC detected a 13% higher number of subjects with at least one adenoma and 59% higher adenomas per subject. CAC is a safe, effective and practical means to improve adenoma detection rates.Clinical Trial RegistrationNCT 01211132.